The Impact of Digital Transformation through Visual Content on Business Activities in Palopo City - Andi Faizah Makmur; Muhammad Alwi; Mahadin Shaleh; Andi Farhami Lahila M (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The accelerating digital transformation has driven significant changes in how businesses market their products and engage with consumers. In Palopo City, the use of visual content, such as product photos, short videos, promotional designs, and visual storytelling, has become an increasingly prominent strategy. However, there is limited research specifically addressing how visual content impacts the business activities of various business actors in the region during the digital transformation process. This study aims to analyze the role of visual content in increasing visibility, sales, and customer relationships as part of the dynamics of digital transformation among businesses in Palopo City. Using a qualitative approach with in-depth interviews and field observations, this study explores the experiences and perceptions of business actors from various sectors. The research findings indicate that visual content serves not only as a promotional tool but also as a means of building brand identity, increasing credibility, and expanding market reach through digital platforms. Furthermore, businesses that are able to adapt visual content consistently and creatively tend to experience a more significant increase in business activity. This study provides a theoretical contribution related to understanding the role of visual content in digital transformation, while also offering practical implications for businesses, supporting institutions, and local governments to optimize digital strategies to drive local economic growth.